SD-WACCM-X Study of Nonmigrating Tidal Responses to the 2019 Antarctic Minor SSW - Chen-Ke-Min Teng; Zhiqiang Fan; Wei Cheng; Yusong Qin; Zhenlin Yang; Jingzhe Sun (Atmosphere, 2025)
The 2019 Antarctic sudden stratospheric warming (SSW) is well captured by the specified dynamics Whole Atmosphere Community Climate Model with thermosphere and ionosphere eXtension (SD-WACCM-X). This SSW is dominated by a strong quasi-stationary planetary wave with zonal wavenumber 1 (SPW1) activity, and nonmigrating tides show great variations. The nonlinear interactions between SPW1 and diurnal, semidiurnal and terdiurnal migrating tides triggered by this SSW also have significant impacts on the variabilities of corresponding nonmigrating tides. This is clearly proven by the fact that the variations of the secondary nonmigrating tides, generated by the nonlinear interaction, show higher correlation during this SSW than those during the non-SSW period. Meanwhile, the SPW1 dominates the nonlinear interactions with diurnal, semidiurnal and terdiurnal migrating tides, and the corresponding secondary nonmigrating tides show concurrent increases with SPW1. In the ionosphere, the nonmigrating tidal oscillations exhibit consistent temporal variabilities with those shown in the neutral atmosphere, which demonstrates the neutral–ion coupling through nonmigrating tides and that nonmigrating tides are significant sources for the short-term ionospheric variability during this SSW event. Specifically, the enhancement of the ionospheric longitudinal wavenumber 4 structure coincides with the increase of the eastward-propagating diurnal tide with zonal wavenumber 3 (DE3), semidiurnal tide with zonal wavenumber 2 (SE2) and terdiurnal tide with zonal wavenumber 1 (TE1). Also, DE3 dominates the influence of nonmigrating tides on the ionospheric longitudinal wavenumber 4 structure during this SSW.